Patients with unilateral patellofemoral pain have altered bone turnover in the painful knee compared to the pain-free knee at rest and after acute knee loading - Rudi Hansen; Bryan Haddock; René B. Svensson; Markus Nowak Lonsdale; Lisbeth Marner; Lene Rørdam; Inge Lise Rasmussen; Christoffer Brushøj; S. Peter Magnusson; Marius Henriksen; Christian Couppé (Osteoarthritis and Cartilage Open)
Objective: The objective of this study was to investigate subchondral bone turnover at rest and after acute loading using Fluorine-18-labeled sodium fluoride (Na[18F]F) Positron Emission Tomography (PET), in patients with unilateral PFP. Design: Twenty-seven patients with unilateral PFP were recruited from the Institute of Sports Medicine Copenhagen. Participants underwent Na[18F]F-PET imaging before and after a bout of single-leg squats. Bone turnover measures, including mean and maximal standardized uptake value (SUVmean and SUVmax), rate of bone perfusion (K1), rate of tracer uptake into bone (Ki), and extraction fraction of tracer absorbed into bone mineral were assessed for patella and trochlea. Results: At rest, the painful knees showed lower SUVmax, K1, and Ki compared to the pain-free knees in the superficial part of the patella. No significant differences were found in the profound part of the patella or trochlea at rest. Following knee loading, the acute increases in SUVmean, SUVmax, Ki and blood flow were reduced in the superficial patella of the painful knees compared to the pain-free knees. In the trochlea, painful knees showed larger increases in SUVmean and Ki in the lateral part, whereas the medial part showed greater increases in K1, Ki, and a larger decrease in extraction fraction after loading. Conclusion: Patella displayed decreased bone metabolism at rest and reduced response to loading in the painful versus pain-free knees. Trochlea in the painful knees showed significantly larger increases in subchondral bone metabolism following knee loading compared to the pain-free knees. These novel findings highlight potential differences in bone turnover between the patellar and trochlear regions.